(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background: Laryngoscopy and endotracheal intubation are noxious stimuli capable of producing a hugespectrum of stress responses such as tachycardia, hypertension, laryngospasm, bronchospasm, raisedintracranial pressure and intraocular pressure. Simultaneously skull pin insertion during neurosurgicaltechnique aggravates the noxious stimulus causing acute hypertension even in an adequately anaesthetizedpatient. These haemodynamic changes are generally temporary without any sequelae in normotensive patients,but can accelerate the development of complications, e.g., myocardial ischemia, arrhythmia, infarction andcerebral haemorrhagein patients with coronary artery disease, hypertension or cerebrovascular disease.Different pharmacological agents are used in order to prevent haemodynamic responses. Intravenous Fentanylhas showed a promising result, preventing the increase in plasma concentrations of catecholamines anddecreasing the central sympathetic outflow. Another agent labetalol, is an unique oral and parenteralantihypertensive drug that is α1 and nonselective β1 and β2 adrenergic antagonist. Objectives: To evaluate the effectiveness of Labetalol-fentanyl for attenuating pressure responses tointubation as well as skull pin insertion in patients undergoing neurosurgery under general anesthesia. Materials & method: This prospective, randomized controlled trial was conducted Department ofAnaesthesia Analgesia and Intensive Care Medicine, Dhaka Medical College Hospital from 18th March 2019to 17thSeptember 2019. Total 60 patients undergone elective neurosurgery and requiring pin insertion wereenrolled for the study and allocated into two groups. Group A: patients given intravenous 0.25 mg/kgLabetalol and fentanyl 2μg/kg combination. Group B patients were given intravenous Fentanyl alone.Following that haemodynamic condition and outcome was assessed at different point of time. Result: Mean age was found to 45.8±11.5 years. It was observed that almost two third (63.3% & 60.0%)patients had ASA grade I in group A and group B respectively. After induction, mean heart rate wasincreases in both group but more in group B. It was 92.4.7±7.8 beat/min and 97.3±7.4 beat/min in group Aand group B respectively. After pin insertion, mean heart rate was 84.1±5.4 beat/min in group A and98.5±85.4 beat/min in group B. after intubation MAP in group-B was statistically significant high(111.4±15.6 mmHg) as compared to group A (99.8±9.5 mmHg) and was unstable upto5 minute time. Thestatistically significant difference between groups was also observed at time of pin insertion (97.5±9.7 mmHgin group A vs. 110.6±12.9 mmHg in group B), after pin insertion (94.9±10.3 mmHg in group A vs. 111.5±10.4mmHg in group B). Intraoperative HR & MAP were almost normal and and remained stabilized in group-Apatients. Conclusion:Labetalol-Fentanyl combination was more effective compared to Fentanyl alone in attenuatingthe pressure responses to intubation and skull pin insertion in neurosurgery. JBSA 2021; 34 (2) : 36-43